POTENTIAL LEGAL RISKS ARISING IN CASH ON DELIVERY (COD) PAYMENT MECHANISM IN E-COMMERCE APPLICATIONS - Hanindita Kusumawardhani Arham; umar haris Sanjaya (Universitas Muhammadiyah Tangerang, 2022)
E-commerce is not only a place to promote goods and services but also for trading and payment.Cash on Delivery (COD) is a payment system in cash the moment the goods have arrived at buyers. The COD payment mechanism causes potential legal risks such as complaints from buyers because the goods that arrived do not match. This is detrimental to the shipping agent. High public interest in using COD payment system for online transactions poses potential risks for sellers, couriers, and buyers. In the COD payment system in e-commerce applications, sellers are often dishonest and commit fraud. Buyers often cancel unilaterally, causing losses for the seller and the courier. The e-commerce party will provide compensation for sellers who have been harmed.